SISTEM PREDIKSI GAJI FRESH GRADUATE ILMU KOMPUTER BERBASIS APLIKASI DESKTOP - Marcellino Calvin Passar, (2023)
Competition in the world of work is increasing every year, everyone is competing to get a job with a salary that matches their expectations, especially for Computer Science Fresh Graduates who must prepare themselves well to be able to compete and be able to meet special criteria to be able to get a salary according to their quality. This final project is made to find out the amount of salary that can be received by Computer Science Fresh Graduates by applying a classification algorithm, namely the K-Nearest Neighbor algorithm based on a desktop application. This algorithm calculates the percentage of self-quality possessed by each Computer Science Fresh Graduate to get the appropriate salary based on data obtained through a Google Forms questionnaire. The final result that is expected in making this final project is to be able to help Computer Science Fresh Graduates to be able to find out the prediction of the salary amount that can be in accordance with their quality.